Shopping Experience of Indonesian Diaspora in Europe Related to Primark’s Reputation and Customer Attitude towards Unethical and Unsustainable Business Practice Brands - Yulia Tricahyaningtyas; Ratu Livani; Susilowati Natakoesoemah (International Journal of Applied Business and International Management, 2023)
This study aims to find out how the public can perceive European fast fashion brands, particularly “Primark” by selling very cheap price of clothes and not environmental friendly. The researchers also want to know what suggestions, messages and further actions addressed by our respondents after they know about Primark’s reputation as well as unethical and unsustainable business practice from other brands, including Primark. This research does not only focus on what customers said about their shopping experience in Primark, basically with the European consumers, but we also applied the questions to Indonesian diasporas who have been or currently staying in Europe. To get deeper understanding yet wider range of expected results, we also interviewed some other Indonesian citizens but who have not been to Europe and asked them about their point of view as well as experience in buying fast fashion and sustainable fashion products. The research method used is descriptive qualitative with data collection techniques through interviews with 6 Indonesian citizens and 2 European citizens (from Germany and France). Those six Indonesian respondents are divided into three categories: 1 Indonesian diaspora currently in Europe, 2 Indonesians who have been to Europe, and 3 others who are passionate in fashion but have not been visited European countries. A result showed that even Primark has bad reputation in public eyes in the past, especially from European consumers and Indonesian diasporas who have been shopping in Primark, however the brand somehow strategically causing consumers to re-influence their brand. Meanwhile, when sustainability commitment newly announced in recent years by Primark to its customers, it someway does not change consumers’ minds and/or the purchase decision to return to shopping there due to strong influence within society (from reference group, family, friends, role, and social status) that has impacted to the consumers’ attitude toward unethical and unsustainable business practices in fashion industry, especially fast fashion brands.